2024
DOI: 10.1021/acs.jpca.3c07801
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Ligand Effects on the Activation and Cleavage of N2 on a Molybdenum Center

Maria V. White,
Emily E. Claveau,
Evangelos Miliordos
et al.

Abstract: Dinitrogen fixation under ambient conditions remains a challenge in the field of catalytic chemistry due to the inertness of N2. Nitrogenases and heterogeneous solid catalysts have displayed remarkable performance in the catalytic conversion of dinitrogen to ammonia. By introduction of molybdenum centers in molecular complexes, one of the most azophilic metals of the transitional metal series, moderate ammonia yields have been attained. Here, we present a combined multiconfigurational/density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Molybdenum-based materials and molecular complexes have been studied extensively due to its presence in nitrogenases. , Our very recent theoretical work on Mo + N 2 and Mo – + N 2 reactions disclosed that Mo can transfer five or six electrons to N 2 cleaving its bond and forming either N 2– Mo­(V)­N 3– or N 3– Mo­(VI)­N 3– . However, the energy of NMoN is higher than that of the Mo­(N 2 ) encounter complex (N 2 weakly interacting with Mo).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molybdenum-based materials and molecular complexes have been studied extensively due to its presence in nitrogenases. , Our very recent theoretical work on Mo + N 2 and Mo – + N 2 reactions disclosed that Mo can transfer five or six electrons to N 2 cleaving its bond and forming either N 2– Mo­(V)­N 3– or N 3– Mo­(VI)­N 3– . However, the energy of NMoN is higher than that of the Mo­(N 2 ) encounter complex (N 2 weakly interacting with Mo).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we discuss the possibility of using molecular catalysts with electron rich metals (dubbed Catalysts with Electron-Rich Metal Atoms or CERMA), formally neutral or anionic. Recent studies of the authors demonstrated by means of quantum chemical calculations that such molecular complexes can have superior performance for the selective conversion of methane to methanol and facile activation of N 2 . The main mechanism and advantages of catalytic cycles mediated by CERMAs are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%